Ultraviolet Photodetector Fabricated from 3D WO3 Nanowires/Reduced Graphene Oxide Composite Material. Issue 1659 (17th February 2014) - Shao, Dali; Yu, Mingpeng; Lian, Jie; Sawyer, Shayla
ABSTRACT: An Ultraviolet (UV) photodetector with high responsivity and relative fast response speed was fabricated from three dimensional WO3 nanowires/reduced graphene oxide (3D WO3 NWs/RGO) composite materials. The 3D WO3 NDs/GN composite was synthesized using a facile three-step synthesis. First, the Na2 WO4 /Graphene Oxide (GO) precursor was synthesized by homogeneous precipitation. Second, the Na2 WO4 /GO precursor was transformed into H2 WO4 /GO composites by acidification. Finally, the H2 WO4 /GO composites were reduced to 3D WO3 NWs/RGO via hydrothermal reduction process. A maximum photoresponsivity of 4.2 A/W at 374 nm was observed under 20 V bias. The UV photodetector showed relative fast transient response, which is at least 2 orders of magnitude faster than UV photodetectors fabricated from WO3 nanowires. The good photoresponsivity and fast transient response are attributed to improved carrier transport and collection efficiency through graphene.